1996
DOI: 10.1111/j.1432-1033.1996.0774h.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Immunodeficiency Virus Type 1 Reverse Transcriptase with Primer tRNALys3 and Affinity Modification of The Enzyme by tRNALys3 Derivatives

Abstract: The recognition of primer tRNA by retroviral reverse transcriptase is a crucial step in the replication of retroviruses. In the complex formed by HIV-1 reverse transcriptase and its natural primer tRNALy", the heterodimeric enzyme, p66/p51, binds two molecules of tRNALy" with different affinities. The same complex but in the presence of a non-complementary template, poly(A), gave higher Kd values. Preincubation of the reverse transcriptase with tRNA at concentrations comparable to the Kd2 value results in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We have previously demonstrated that the binding of a template poly(A) does not prevent the interaction of HIV-1 RT with tRNA Lys3 (41). Here we showed that, in the presence of poly(A), the tRNA derivatives were used as primers by HIV-1 RT.…”
Section: Discussionmentioning
confidence: 68%
“…We have previously demonstrated that the binding of a template poly(A) does not prevent the interaction of HIV-1 RT with tRNA Lys3 (41). Here we showed that, in the presence of poly(A), the tRNA derivatives were used as primers by HIV-1 RT.…”
Section: Discussionmentioning
confidence: 68%